Natural Resources, Institutional Quality, and Economic Growth: an African Tale - (:unkn) unknown (My University, 2020)
This study investigates the role of institutions in the relationship between natural resources and economic growth using panel data from 44 African countries over the period 1996–2016. We use natural resource rents as a percentage of gross domestic product (GDP) and the share of ores and metals exports in total merchandise exports as variables for natural resources. To check for endogeneity, heterogeneity, and nonlinearity, we undertake cross-sectional instrumental variable analysis, system dynamic panel-data instrumental variable regression, and panel smooth transition regression. The relationship between natural resources and economic growth varies for indicators of institutional quality and the measure for natural resources.
Keywords: African Research